2006
DOI: 10.1111/j.1399-0004.2006.00613.x
|View full text |Cite
|
Sign up to set email alerts
|

Non‐syndromic, autosomal‐recessive deafness

Abstract: Non-syndromic deafness is a paradigm of genetic heterogeneity with 85 loci and 39 nuclear disease genes reported so far. Autosomal-recessive genes are responsible for about 80% of the cases of hereditary non-syndromic deafness of pre-lingual onset with 23 different genes identified to date. In the present article, we review these 23 genes, their function, and their contribution to genetic deafness in different populations. The wide range of functions of these DFNB genes reflects the heterogeneity of the genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
152
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(164 citation statements)
references
References 265 publications
(329 reference statements)
3
152
0
8
Order By: Relevance
“…It accounts for approximately 40-50% of overall mutant alleles of the GJB2 gene in deaf patients. 37 Earlier, the large-scale research covering 17 European countries demonstrated that the average carrier frequency of c.35delG in Europe was 1.96% (1 of 51), with a variation from 1.26% (1 of 79) in Central and northern Europe to 2.86% (1 of 35) in southern Europe. 7 Further, the gradient of increase in c.35delG frequency from north to south has been confirmed in the meta-analysis of the carrier frequency of c.35delG in various European populations.…”
Section: Mutation C35delgmentioning
confidence: 99%
“…It accounts for approximately 40-50% of overall mutant alleles of the GJB2 gene in deaf patients. 37 Earlier, the large-scale research covering 17 European countries demonstrated that the average carrier frequency of c.35delG in Europe was 1.96% (1 of 51), with a variation from 1.26% (1 of 79) in Central and northern Europe to 2.86% (1 of 35) in southern Europe. 7 Further, the gradient of increase in c.35delG frequency from north to south has been confirmed in the meta-analysis of the carrier frequency of c.35delG in various European populations.…”
Section: Mutation C35delgmentioning
confidence: 99%
“…In addition, children with cochlear implants show significantly more comorbidity [1]. Hereditary hearing loss occurs in approximately 1/2,000 newborns [2]. More than 50% of pre-lingual deafness in developed countries is attributed to monogenic defects [3] and of these, 50% of nonsyndromic recessive cases are caused by mutations in the GJB2 gene (Connexin 26) [4].…”
Section: Introductionmentioning
confidence: 99%
“…Since 1994, 52 loci associated with recessive hearing loss (HL) have been mapped, and 23 different genes have been identified (The Hereditary Hearing Loss Homepage: http: webhost.ua.ac.be/hhh; Khan, et al, 2006;Petersen & Willems, 2006;Petit, 2006). In spite of this extensive genetic heterogeneity, a single locus, DFNB1 (13q11-q12; OMIM 220290), accounts for up to 50% of nonsyndromic autosomal recessive cases.…”
Section: Introductionmentioning
confidence: 99%